Inside the black box: Intra-household inequality and a gendered pandemic - Deepak Malghan; Hema Swaminathan (Luxembourg Income Study (LIS), 2020)
Emerging evidence suggests that COVID-19 has amplified existing gender divisions that disadvantage women. What is the appropriate unit of analysis to study the gendered impact of a pandemic? The study of gendered inequality - especially labor market opportunities and outcomes - has for the large part relied on population wide differences between men and women. Using over four decades of global data (n =2.85 million couple units, from 45 countries in the LIS repository) we show that intra-household earnings inequality within a household is systemic, prevalent across disparate societies, and across the entire earnings distribution. Our analysis shows why accounting for intra-household gender inequality is crucial to ameliorating the pandemic's gendered impact.
Keywords: 330; Intra-household inequality; earnings inequality; pandemic; lockdown; gender inequality; LIS database